2021
DOI: 10.2355/isijinternational.isijint-2020-684
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Characteristics of Various Oxide Inclusions in Molten Steel Containing Rare Earth Element under Different Deoxidation Conditions

Abstract: Comprehensive investigation of agglomeration behavior of oxide inclusions in steel-containing rare earth (RE) under different deoxidation conditions is essential for improving the nozzle-clogging problem during continuous casting. The present study first optimized the thermodynamic model by supplementing thermodynamic data of the RE-compound to study the formation of various inclusions in the Ce-Si-Al-O system. On this basis, laboratory-scale experiments with different deoxidation conditions were designed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…18) In order to alleviate the harm of high melting point and large-sized inclusions in molten steel, the two methods of modifying them to liquid ones or to disperse ones are considered to be effective. In our earlier study, 19) stable spherical SiO 2 -Al 2 O 3 -RE 2 O 3 liquid inclusions were controlled in RE-Si-Al-O system. Besides Si and Al, Mg is a common deoxidizer in the steelmaking process, which is capable of modifying the original inclusions in molten steel.…”
Section: Effect Of Cerium and Magnesium Addition On Evolution And Par...mentioning
confidence: 85%
See 1 more Smart Citation
“…18) In order to alleviate the harm of high melting point and large-sized inclusions in molten steel, the two methods of modifying them to liquid ones or to disperse ones are considered to be effective. In our earlier study, 19) stable spherical SiO 2 -Al 2 O 3 -RE 2 O 3 liquid inclusions were controlled in RE-Si-Al-O system. Besides Si and Al, Mg is a common deoxidizer in the steelmaking process, which is capable of modifying the original inclusions in molten steel.…”
Section: Effect Of Cerium and Magnesium Addition On Evolution And Par...mentioning
confidence: 85%
“…[35][36][37] The agglomeration characteristics of various inclusions have been investigated by in-situ observation combined with quantitative calculation. 19,37,38) According to experimental data in these studies, the agglomeration ability of the inclusions is depicted in Fig. 14 including the data from the literatures, 38,39) where the larger the attractive force and the maxing acting distance, the stronger the agglomeration ability between inclusions.…”
Section: Evolution Behavior Of Cluster-like Cealo 3 Inclusionsmentioning
confidence: 99%
“…Ahn et al [ 22 ] found obvious increase in the impact energy of the duplex stainless steel and the brittle‐to‐ductile transition temperature slightly decreased by ≈10 °C with the addition of Ga. Du et al [ 23 ] found that the impact toughness of the CrNiMnMo steel lining board improved greatly with the addition of cerium and the impact toughness increased by 22% with the fracture mode of being ductile. Wang et al [ 24,25 ] indicated through thermodynamic calculations that the denaturation sequence of Ce inclusions was Al 2 O 3 → CeAlO 3 → Ce 2 O 3 + Ce 2 O 2 S → Ce 2 O 2 S. The study could provide theoretical guidance for inclusion‐controlling perspective under different deoxidation conditions of the RE‐containing steel. Liu et al [ 26 ] found that the RE addition contributed to modifying irregular MnS and Al 2 O 3 inclusions into ellipsoidal RE‐inclusions.…”
Section: Introductionmentioning
confidence: 94%
“…Ahn et al [22] found obvious increase in the impact energy of the duplex stainless steel and the brittle-to-ductile transition temperature slightly decreased by %10 °C with the addition of Ga. Du et al [23] found that the impact toughness of the CrNiMnMo steel lining board improved greatly with the addition of cerium and the impact toughness increased by 22% with the fracture mode of being ductile. Wang et al [24,25] indicated through thermodynamic calculations that the denaturation sequence of Ce DOI: 10.1002/srin.202200883…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] At present, the main addition method of rare earth during steelmaking is added in the refining process. [9,13] However, this method will cause a clogging effect in the submerged entry nozzle, which significantly limits the continuous casting time and poses a threat to casting safety seriously. [14][15][16] In order to prevent clogging, a method for introducing feeding rare earth directly from the continuous casting mold has been proposed.…”
Section: Introductionmentioning
confidence: 99%